The Influence of the Complex Bacterial Preparation Azogran on Some Physiological-Biochemical Properties and Productivity of Potato Plants Infected by the Potato Virus X - Parkhomenko, N.Y.; Kurdish, I.K.; Пархоменко, Н.Й.; Курдиш, І.К. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
The problem of increasing the yield of cultivated plants attracts the attention of specialists and prompts scientists to study viral plant diseases as one of the causes of significant crop losses. A virus is an endogenous parasite that, having entered plant cells, uses the functions of cell organoids and biosystems for its reproduction, which leads to plant disease and a decrease in their productivity. One of the promising approaches to reducing viral damage to plants is the use of microbial antiviral preparations. The complex bacterial preparation Azogran, developed at the Institute of Microbiology and Virology of the National Academy of Sciences of Ukraine, is based on the interaction of phosphate-mobilizing bacteria Bacillus subtilis IMV B-7023, nitrogen-fixing bacteria Azotobacter vinelandii IMV B-7076, and clay mineral — bentonite. Phosphate-mobilizing bacteria and nitrogen-fixing bacteria significantly improve the growth and development of plants, essentially increasing the yield of agricultural crops. However, the effect of Azogran on the development and yield of potato plants infected with the X-virus has not been sufficiently studied. Taking this into account, the aim of the work was to study the effect of the complex bacterial preparation Azogran on the growth, some physiological and biochemical properties, and productivity of potato plants, uninfected and infected by the potato virus X. Methods. Microbiological (obtaining the bacterial preparation Azogran, used in granular form (0.25 g)), virological (isolation of potato virus X, inoculation of plants with potato virus X), serological (testing for the presence or absence of the virus), biochemical (determination of chlorophylls a, b and carotenoids), spectrophotometric, and statistical analysis. Results. In the conducted experiments, the Azogran was used in granular form in the amount of one and two granules. The effectiveness of the use of the preparation, which stimulates the intensive growth of plants of two varieties of potatoes (early variety Spokusa and medium variety Diva), which leads to an increase in their yield, is shown. The positive effect of Azogran was observed on the development of both infected and non-infected plants. It was found that when two granules of the preparation were applied, the yield of potatoes of the Diva variety increased by 27.02%, and the yield of potatoes of the Spokusa variety under the same conditions increased by 29.46%. A similar effect of Azogran was observed on plants infected with the potato virus X, only to a lesser extent: in the Diva variety, the yield was 16.3% higher compared to the control (control — plants not infected by the virus), and in the Spokusa variety it was higher by 22.59%. When studying the content of chlorophylls a and b and carotenoids in virus-infected potato plants, it was established that the content of chlorophylls at different stages of virus infection was different, but the content of chlorophylls and carotenoids was higher in plants bacterized with Azogran. Conclusions. The complex bacterial preparation Azogran has a positive effect on the development of uninfected and infected plants, reducing the harmfulness of viral infections and contributing to the increase in potato productivity. Azogran can be successfully used in crop production to increase the quality and quantity of crop yields.